Novel proteins from designed combinatorial libraries - Hecht, Michael (Henry Stewart Talks, 2007)
Novel proteins can be devised using either rational/computational approaches or random/combinatorial methods, Description of a hybrid approach that combines rational and combinatorial methods: libraries of novel proteins, Combinatorial diversity, Random vs. focused libraries, Amphiphilic alpha-helices and beta-strands, Binary patterning of polar and non-polar amino acids, Genetic encoding of combinatorial mixtures of polar and non-polar amino acids, Design of libraries of novel 4-helix bundles, Library construction and expression in vivo, Dynamic vs. wellordered protein structures, Second generation libraries, Biophysical characterization, Solution structure of native-like 4-helix bundle proteins from designed libraries, Functionally active proteins including cofactor binding proteins, peroxidases and esterases, Designed libraries of beta sheet proteins: amyloid-like fibrils, monomeric beta-sheet proteins and novel biomaterials
Archived at 2017/04/03